2016
DOI: 10.1038/nature19342
|View full text |Cite
|
Sign up to set email alerts
|

m6A RNA methylation promotes XIST-mediated transcriptional repression

Abstract: The long non-coding RNA X-inactive specific transcript (XIST) mediates the transcriptional silencing of genes on the X chromosome. Here we show that in human cells XIST is highly methylated with at least 78 N6-methyladenosine (m6A) residues—a reversible base modification of unknown function in long non-coding RNAs. We show that m6A formation in XIST, as well as in cellular mRNAs, is mediated by RNA binding motif protein 15 (RBM15) and its paralogue RBM15B, which bind the m6A-methylation complex and recruit it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

51
1,666
8
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,440 publications
(1,799 citation statements)
references
References 53 publications
51
1,666
8
3
Order By: Relevance
“…Recent findings from Jaffrey's lab showed that the abundant deposition of m 6 A is mediated by the methylation complex WTAP-METTL3, which is recruited to XIST-specific sites by RBM15 and RBM15B RNAbinding proteins (Patil et al, 2016). These findings reveal that this highly abundant post-transcriptional mark ensures YTHDC1 recruitment to at least a few of the methylated XIST residues and functionally enables the transcriptional repression effects of XIST on X chromosome genes.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Recent findings from Jaffrey's lab showed that the abundant deposition of m 6 A is mediated by the methylation complex WTAP-METTL3, which is recruited to XIST-specific sites by RBM15 and RBM15B RNAbinding proteins (Patil et al, 2016). These findings reveal that this highly abundant post-transcriptional mark ensures YTHDC1 recruitment to at least a few of the methylated XIST residues and functionally enables the transcriptional repression effects of XIST on X chromosome genes.…”
Section: Introductionmentioning
confidence: 93%
“…Adenosine methylation m 6 A deposition in mRNA and miRNA: the story so far m 6 A is the most prevalent internal modification found in mRNA from viruses to mammals, but also occurs in small non-coding RNA (ncRNA) and long non-coding RNA (lncRNA) in many eukaryotic species (Patil et al, 2016;Yue et al, 2015). m 6 A is enriched at 3′ untranslated regions (UTRs) near stop codons, within long internal exons, in intergenic regions and introns and at 5′ UTRs ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 XIST is m 6 A-methylated by METTL3, which is recruited to XIST through the proteins RBM15 and RBM15B. In an inducible XIST expression system, loss of METTL3 allows for induction of XIST, but its gene silencing function is impaired.…”
Section: Mrnamentioning
confidence: 99%
“…Cap-independent translation initiation was enhanced by 5′ UTR methylation [47]. m A marks and impairs XIST-mediated gene silencing [49].…”
mentioning
confidence: 99%